Fostering Innovation through Co-Creation: A Journey Towards Farmer Inclusion - Bernado, Eisen (CGIAR, 2024)
In a world facing the challenges of climate change and the need for sustainable food systems, innovation and collaboration have become indispensable. One approach that holds great promise is co-creation, a dynamic process that brings together diverse stakeholders to design and develop solutions collaboratively. The CGIAR Initiative on Low-Emission Food Systems conceived the ‘Living Labs for People’ as a framework to include farmers and other stakeholders in the co-creation process. Through this process and with support from the EU-IFAD project “Agroecological Transitions for Building Resilient, Inclusive Agriculture and Food Systems (TRANSITIONS)”, farmers and field agents participated in the co-creation of a suite of three digital tools to support climate-informed agroecological decision making. The aim is to promote inclusion of farmers, especially women and marginalised groups, and other stakeholders through innovation at various levels and stages, supporting low-emission transitions in food systems. Food systems are a significant contributor to greenhouse gas (GHG) emissions, necessitating a transformation in practices all along the value chain from production to consumption. The goal is to ensure that solutions not only protect the environment but also support food security and economic sustainability, particularly for disadvantaged farmers.